The effects of decomposing mangrove leaf litter and its tannins on water quality and the growth and survival of tiger prawn (Penaeus monodon) post-larvae - sri rejeki sulaiman; MARCEL MIDDELJANS; Lestari Lakhsmi Wiidowati; Restiana Wisnu Ariyati; TITA ELFITASARI; Roel H Bosma (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Rejeki S, Middeljans M, Widowati LL, Ariyati RW, Elfitasari T, Bosma RH. 2019. The effects of decomposing mangrove leaf litter and its tannins on water quality and the growth and survival of tiger prawn (Penaeus monodon) post-larvae. Biodiversitas 20: 2750-2757. Shrimp farming in Demak, Indonesia is often practiced in silvo-aquaculture systems in which mangrove trees are planted on pond bunds. As such, mangrove leaves and its substrates may have impact on penaeid shrimp production. In this area, mangrove re-growth proceeded with Avicennia marina while planting is mostly done with Rhizophora apiculata. We compared the effects of decomposing fresh leaves of A. marina and R. apiculata on water quality and on the performance of Penaeus monodon postlarvae (PL). A hundred of PL21 (postlarvae aged 21 days with weight of 0.28 g) were stocked in each of 30 aerated tanks containing 800 liters of brackish water (salinity of 21 ppt) for 37 days. Five treatments with three replicates for each mangrove species were assigned by adding into the tanks of 0.125, 0.25, and 0.5 g L-1 of air-dried leave, 0.125 of g L-1 minced leave and 0.125 g L-1 of leachate of minced leaves. The PLs were fed 3 times daily with pellets at 10 % of initial total body weight. Water quality parameters were recorded daily. Tannin, H2S and NH3-N concentrations were measured every ten days. Prawn's body weight (BW) was measured and specific growth rate (SGR, % day-1) and survival rate (SR, %) were calculated after the end of experiment. Results were analyzed with ANOVA and Pearson's correlation. The results showed that tannin in decomposing mangrove leaf litter up to a concentration of 0.5 mg g-1 did not have a significant effect on water quality and on the growth and survival of P. monodon PL. However, increasing leaf litter concentrations showed an increase in NH3-N concentration due to organic matter degradation. The accumulation of NH3-N may have caused the slow growth of shrimp PL in A. marina treatment. Shrimp PL in leaf litter leachates treatment has a higher growth rate than those PL in regular leaf litter in relation to nutritional value. Survival and growth varied from 62 ±14 to 70 ± 8% and 3.1±2.1 to 5.5±1.2% day-1, respectively. Although decomposing mangrove leaves of A. marina and R. apiculata had no toxic effects on P. monodon PL up to a concentration of 1.25 g L-1, but causing severe mortality for shrimp in tanks without water exchange. As a conclusion, the present of mangrove leaves in brackish water ponds with insufficient water exchange can be harmful to shrimps. However, if the water exchange is good, decomposed mangrove leaves can become organic fertilizer that beneficial for the growth of natural food for the shrimps